Equilibrium and growth in the world economy. - Nurkse, Ragnar (Harvard University Press, Cambridge, Massachusetts, 1961)
Essays on various economic issues
"The writings of Ragnar Nurkse": p. [365]-369.
obn 25/10/2019
Loans
Keywords: Economics; International economic relations; Economic development